In vitro efficacy of leaf extracts of certain indigenous medicinal plants against brown leaf spot pathogen of rice - R.D. KHULBE, G.S. BISHT* and (Indian Phytopathology, 2002)
Leaf extracts from 10 plants were evaluated for their efficacy in controlling growth of Drechslera oryzae [Cochliobolus miyabeanus] in vitro. All extracts exhibited fungitoxic properties and significantly reduced mycelial growth compared with the control. Max. inhibition was recorded by extracts from Juglans regia followed by Allium sativa, Origanum vulgare and A. wallichii.